2008
DOI: 10.1002/ejoc.200800891
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Efficient Approach to PNA Monomers Compatible with Fmoc‐Mediated Solid‐Phase Synthesis Protocols

Abstract: A straightforward synthesis of orthogonally protected PNA monomers is described. Protected aminoethylglycine (Aeg) monomers were efficiently prepared by reductive amination of N-Fmoc-glycinaldehyde with glycine methyl ester and the subsequent acylation of the free amine with N-bis-Boc-protected nucleobase acetic acids. The exocyclic amine group of the nucleobases, including the notoriously difficult-to-protect guanine nucleobase, was protected with a bis-Boc carbamate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 52 publications
2
62
0
Order By: Relevance
“…2-methylene-1,3-propanediol (6), >97% pure (Aldrich) Vinyl acetate, >99% pure (Aldrich) Lipase acrylic resin from Candida antarctica, recombinant, expressed in Aspergillus niger, (CAL-B, Sigma, L4777) Hoveyda-Grubbs Catalyst 2nd Generation, >97% pure (Aldrich) Activated carbon (Merck), optional Phosphate buffer (0.1 M, pH 7) bis-Boc-adenine (Porcheddu et al, 2008) Triphenylphosphine (PPh 3 ), >99% pure (Aldrich) Diisopropyl azodicarboxylate (DIAD), >94% pure (Alfa aesar) Hydrochloric acid (HCl): 1 M in methanol Ethanol (EtOH), analytical grade Compact Multifunctional Digital Ultrasonic Cleaner, Elmasonic P30H Ice bath…”
Section: Additional Materials (Also See Basic Protocol 1)mentioning
confidence: 99%
“…2-methylene-1,3-propanediol (6), >97% pure (Aldrich) Vinyl acetate, >99% pure (Aldrich) Lipase acrylic resin from Candida antarctica, recombinant, expressed in Aspergillus niger, (CAL-B, Sigma, L4777) Hoveyda-Grubbs Catalyst 2nd Generation, >97% pure (Aldrich) Activated carbon (Merck), optional Phosphate buffer (0.1 M, pH 7) bis-Boc-adenine (Porcheddu et al, 2008) Triphenylphosphine (PPh 3 ), >99% pure (Aldrich) Diisopropyl azodicarboxylate (DIAD), >94% pure (Alfa aesar) Hydrochloric acid (HCl): 1 M in methanol Ethanol (EtOH), analytical grade Compact Multifunctional Digital Ultrasonic Cleaner, Elmasonic P30H Ice bath…”
Section: Additional Materials (Also See Basic Protocol 1)mentioning
confidence: 99%
“…Using this method, mass marker ions can readily be distinguished from the matrix ions. The modifications were added to the amino-terminus of the PNA, under standard peptide-coupling conditions during solid-phase synthesis, [20][21][22] to make three different types of PNA probe for comparison in the hybridization assay ( Table 1) . Detection of the G to A transition mutation at the W1282X locus requires a cytosine base at the site of mutation for the wild-type probe and thymine base for the mutant.…”
Section: Peptide Nucleic Acid Probes With Charged Photocleavable Massmentioning
confidence: 99%
“…Another advantage of the Boc protection group is that its acidolytic removal is less sensitive to steric factors and can also be removed under neutral conditions (Hwu et al, 1996;Siro et al, 1998). In contrast, a few studies have recently been reported that apply the Boc group in the protection of nucleobase (Sikchi and Hultin, 2006;Porcheddu et al, 2008). As described by Porcheddu et al (2008), solubility of nucleobases, including guanine, was increased in some organic solvents after protected by Boc groups.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a few studies have recently been reported that apply the Boc group in the protection of nucleobase (Sikchi and Hultin, 2006;Porcheddu et al, 2008). As described by Porcheddu et al (2008), solubility of nucleobases, including guanine, was increased in some organic solvents after protected by Boc groups. In addition, some results in our previous study (Yang et al, 2011) demonstrated a very good improvement in coupling purine derivatives under Mitsunobu conditions.…”
Section: Introductionmentioning
confidence: 99%